Hubungan Antara Faktor Penggunaan Gawai dengan Progresivitas Miopia Pada Anak di Rumah Sakit Puri Cinere dan Tinjauannya Menurut Pandangan Islam - Difa Fitria kusnadi; Saskia Nassa Mokoginta; Tri Agus; Ali Ma’sum (Publikasi Indonesia, 2026)
Myopia is one of the most common refractive disorders among children and is a leading cause of visual impairment worldwide. The increasing use of digital devices among children has raised concerns about its impact on myopia progression. This study aims to analyze the relationship between device-use duration and viewing distance with myopia progression in children at Puri Cinere Hospital and to examine these findings from an Islamic perspective. This quantitative cross-sectional study included 37 children aged 5–17 years diagnosed with myopia and possessing complete medical records for 2024–2025. Data were collected through medical records and questionnaires assessing device-use habits. Bivariate analysis using the Chi-Square test revealed a significant relationship between device-use duration and myopia progression (p = 0.020), as well as between viewing distance and myopia progression (p = 0.002). Children who used digital devices for more than four hours per day and at distances below 50 cm were at higher risk of experiencing myopia progression. From an Islamic viewpoint, maintaining eye health is an obligation, as emphasized in Surah Yunus verse 44, which warns against self-harm caused by harmful habits. This study highlights the importance of visual ergonomics education, parental supervision of device use, and increased outdoor activities to help prevent myopia progression in children.